The Influence of Group Investigation and Virtual Box Learning Media to Students’ Activeness. - Umbarwati, Rini; Basori, Basori; Sucipto, Taufiq Lilo Adi (Universitas Sebelas Maret, 2017)
This research aims to know whether the implementation of Group Investigation learning model and Virtual Box learning media can increase students activeness and learning achievement on the subject of operating system class X Multimedia (MM) SMK N 6 Surakarta. This research used classroom action research with two cycles, each cycle consisted of planning, implementation, observation, and reflection of teaching and learning activities. The subject of this research is the students of class X MM1 SMK N 6 Surakarta which numbered 32 students. Data collection technique that used were interview, observation, documentation and test. Meanwhile analysis technique implemented through comparative analysis and descriptive qualitative. This class action research carried out from December 2015 until June 2016. The result of research shows that the implementation of Group Investigation learning model and Virtual Box learning media can increase students activeness and learning achievement on the operating system subject. This can be proved on the pre-cycle activities observation, the percentage of students activeness is 52,87%, after implementation of Group Investigation learning model and Virtual Box in the first cycle increased by 77,87%, then in the second cycle increased to 86,72%. While the result of students learning achievement also increased from the value of each cycle test. On pre-cycle the average learning achievement for cognitive domain 62,5%, affective 65,27%, and psychomotor 73,44%. The average of learning achievement increased for cognitive domain became 73,38%, affective 71,5%, and psychomotor 75% after the implementation of Group Investigation learning model and Virtual Box at the first cycle. At the second cycle increased for cognitive domain to 87,5%, affective 82,52%, and psychomotor 80,47%. Research conclusion that the implementation of Group Investigation learning model and Virtual Box learning media could increase the students activeness and learning achievement on the subject of operating system class X MM SMK N 6 Surakarta.This work is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.